2022
DOI: 10.1007/s11750-022-00645-1
|View full text |Cite
|
Sign up to set email alerts
|

Day-ahead market bidding taking the balancing power market into account

Abstract: Generation companies with controllable units put considerable analysis into the process of bidding into the day-ahead markets for electricity. This article investigates the gain of coordinating price-taking bids to the day-ahead electricity market (DA) and sequentially cleared energy-only markets, such as the Nordic balancing market (BM). A technically detailed case study from the Nordic market is presented. We find that coordinated bidding is hardly worthwhile under current market conditions, but that only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The literature on balancing volumes and imbalance prices in the Norwegian and Nordic power markets is scarce [8,10,11,18]. Klaeboe et al [10] found that coordinated bidding between the day-ahead and balancing market is currently not profitable, but it might become so with increased volumes and imbalance price premiums, i.e., differences between dayahead price and imbalance price. However, their study focused on imbalance prices and not on predicting balancing volumes for production planning.…”
Section: Related Work and Our Contributionmentioning
confidence: 99%
“…The literature on balancing volumes and imbalance prices in the Norwegian and Nordic power markets is scarce [8,10,11,18]. Klaeboe et al [10] found that coordinated bidding between the day-ahead and balancing market is currently not profitable, but it might become so with increased volumes and imbalance price premiums, i.e., differences between dayahead price and imbalance price. However, their study focused on imbalance prices and not on predicting balancing volumes for production planning.…”
Section: Related Work and Our Contributionmentioning
confidence: 99%
“…However, the authors hypothesize that weather may be influential for models incorporating consumption forecasts together with temperature forecasts or if the power systems had a greater share of renewable wind or solar production. Klaeboe et al (2022) studied bidding strategies between dayahead and balancing markets for hydro-power producers in Norway. They concluded that coordinated bidding between the two markets is currently not profitable, but might be with increased volumes and price premiums.…”
Section: The Nordic Balancing Marketmentioning
confidence: 99%
“…Klaeboe et al [15] studied bidding strategies between day-ahead and balancing markets for hydro-power producers in Norway. They concluded that coordinated bidding between the two markets is currently not profitable, but might be with increased volumes and price premiums.…”
Section: The Nordic Balancing Marketmentioning
confidence: 99%